Efektivitas Teknik Pemodelan Terhadap Keterampilan Menulis Teks Eksplanasi Siswa Kelas VIII 1 SMP Negeri 1 Batang Anai - Jessy Mutiara Helda; Trisna Helda; Ria Satini (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2023)
This study aims to describe the effectiveness of modeling techniques on the skills of writing explanatory texts for class VIII.1 students of SMP Negeri 1 Batang Anai. This type of research is quantitative research. This research method is experimental research. The research design used is the One-Group Pretest-Posttest Design. The population in this study were class VIII students of SMPN 1 Batang Anai for the 2021/2022 academic year, totaling 240 people consisting of 8 classes. The sample in this study was class VIII.1. The independent variable is modeling techniques while the dependent variable is writing explanatory text. The instrument used in this research is a performance test. namely the performance test of writing explanatory text. The results of this study are because tcount>ttable (5.13> 1.70) so that the use of Modeling Techniques influences the writing skills of explanatory texts for class VIII.1 students of SMP Negeri 1 Batang Anai.